Symbolic Values Of Historical Affiliation And Their Intellectual And Performance Behavioral Reflection In Contemporary Interior Design - Kareem Hasan, Yasir; Zaki Abudlhameed, Shaima (Opción, 2019)
Interior design seeks different intellectual attitudes to achieve the desired integration in the design products of the interior environments, as each inter- nal space is linked to expressive, aesthetic and functional values so that they constitute an important role in the design process, through the embodiment of symbols and the investment of their meanings in the design action, which generates in the recipient intellectual reflections Behavioral, individual or col- lective performance, as it represents a specific historical culture. Design action has an active role in intellectual development, and in turn it shows the inten- tionality of the interior designer in the spaces of buildings and to translate through it the discursive design style that enriches the expressive sense of the recipient and gives him a feeling of pleasure through the mental images asso- ciated with those symbols. Therefore, the research problem can be formulated as follows: A gap exists in the embodiment of the symbolic values of historical affiliation within the formal formulations of the internal spaces in the hotel reception halls, leading to a kind of communicative intellectual disconnection between the recipient and the historical legacy and the extent to which this effect is translated into his behavioral action.